2016
DOI: 10.4995/raet.2016.5731
|View full text |Cite
|
Sign up to set email alerts
|

Sistema para el Seguimiento del funcionamiento de ecosistemas en la Red de Parques Nacionales de España mediante Teledetección

Abstract: Resumen: La gestión de las áreas protegidas en el actual contexto de cambio global requiere de aproximaciones que permitan caracterizar y seguir el funcionamiento de los ecosistemas. La teledetección ofrece herramientas para ello, ya que proporciona índices que informan reiteradamente y para grandes porciones de territorio, de los intercambios de materia y energía que tienen lugar entre la biota y la superficie terrestre. Considerando este principio, y la cada vez mayor disponibilidad de información satelital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…Ecological research based on spectral vegetation indices plays an important role in biodiversity conservation 315 (Cabello et al, 2012;Pettorelli, 2016Pettorelli, , 2018 and management (Pelkey et al, 2003;Cabello et al, 2016) and for the study of biodiversity and ecosystems responses to environmental changes (Alcaraz-Segura et al, 2017; Pérez-Luque et al 2015). In fact, numerous studies have demonstrated the usefulness of satellite image time series to evaluate the functional changes in ecosystems at regional scale (Alcaraz-Segura et al, 2010) and at the protected area level (Alcaraz-Segura et al, 2009;Lourenço et al, 2018).…”
Section: Data Applications For Research and Conservation / Example Ofmentioning
confidence: 99%
“…Ecological research based on spectral vegetation indices plays an important role in biodiversity conservation 315 (Cabello et al, 2012;Pettorelli, 2016Pettorelli, , 2018 and management (Pelkey et al, 2003;Cabello et al, 2016) and for the study of biodiversity and ecosystems responses to environmental changes (Alcaraz-Segura et al, 2017; Pérez-Luque et al 2015). In fact, numerous studies have demonstrated the usefulness of satellite image time series to evaluate the functional changes in ecosystems at regional scale (Alcaraz-Segura et al, 2010) and at the protected area level (Alcaraz-Segura et al, 2009;Lourenço et al, 2018).…”
Section: Data Applications For Research and Conservation / Example Ofmentioning
confidence: 99%
“…We used one-year of cloud-free time series of FAPAR (see Section 2.2.1) to describe, classify, and map the intra-annual functional activity of the vegetation cover considering existing methodologies for functional characterisations of ecosystems [1,[4][5][6][7][8][9]11].…”
Section: Analysis and Characterisation Of Functional-trait Dynamicsmentioning
confidence: 99%
“…The characterisation of ecosystems based on functional-trait dynamics derived from remotely sensed data complements structural studies for describing the heterogeneity of ecosystems [1,3]. Several studies have been developed for characterising functional activity of vegetation cover at a regional scale [1,[4][5][6][7][8][9]11]. Most of these studies covered large regional scales, with remote sensors of medium and low spatial resolution (e.g., MODIS and NOAA/AVHRR), where seasonal dynamics were characterised using the NDVI or the Enhanced Vegetation Index (EVI) as proxies of the FAPAR.…”
Section: Analysis and Characterisation Of Functional-trait Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…En este contexto se ha utilizado la teledetección, que ha demostrado ser efectiva en análisis de diferentes coberturas: vegetación (Nie et al, 2018), agua (Di Vittorio y Georgakakos, 2018) y suelo (Bansal et al, 2018), ya que ofrece herramientas para caracterizar y seguir el funcionamiento de los ecosistemas, debido a que proporciona índices que informan reiteradamente de los intercambios de materia y energía que tienen lugar entre la biota y la superficie terrestre (Cabello et al, 2016); es decir, que las imágenes satelitales tienen el potencial de proveer valiosa información para la gestión y conservación de los bofedales (García y Lleellish, 2012). En este sentido las imágenes Landsat se han utilizado en distintos estudios de humedales, debido a que es un sistema de satélites diseñados y operados para observar repetidas veces la cubierta de la Tierra con una resolución moderada (Halabisky et al, 2016).…”
Section: Introductionunclassified